Pengaruh Dana Pihak Ketiga (DPK) dan Non-Performing Loan (NPL) Terhadap Penyaluran Kredit pada PT. Bank Perkreditan Rakyat Indonesia Periode 2011-2017 - Ni Luh Putu Santi Aristyani; Kompiang Bagiada; I Nyoman Senimantara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2019)
The aims of this research is to find out how the influence of Third Party Funds (DPK) and Non-Performing Loans on lending to PT. Rural Banks for the 2011-2017 period. The data analysis technique used is multiple linear regression with the SPSS for Windows application. The results of the analysis show that partially third party funds (DPK) have a positive and significant effect on lending and non-performing loans have a negative and significant effect on lending to PT. Rural banks.